The Effect of Google Classroom-Assisted Realistic Mathematics Education Approach on Students’ Mathematical Reasoning Ability - Sopyan, Asep; Hidayat, Wahyu; Rohaeti, Euis Eti (IKIP Siliwangi, 2024)
Mathematical reasoning is an important aspect, but there are still many students who are weak when it comes to mathematical reasoning. Factors that affect the level of mathematical reasoning of low students, including: a) students easily forget the material taught; b) the student has no idea in completing it; c) students are not careful in understanding the problems in the problem; d) students do not understand which formula will be used in solving the problem; e) Students do not understand the concept of the material. This research aims to determine whether or not there is an influence of the approach realistic mathematics education helpgoogle classroomon mathematical reasoning abilities. Quantitative Approach method used in this researchpre-experimental design with one group pretest posttest design. The research subject is the experimental class. Data collection was carried out with pretest and posttest data on the mathematical reasoning abilities of grade 7 students at one of the junior high schools in Purwasari district, kabupaten Karawarang. Data analysis techniques in this study that is analyze the scores of pretest and posttest results students by t-test for 2 dependent samples (Paired Sample T-Test) done with the help of IBM SPSS 21 software. The research results show that there is value of sig 0,000 < 0,05 which means a positive influence approach realistic rathematic education help google classroomon ability students' mathematical reasoning. Based on the result, we can be concluded that there is a positive influence of the approach realistic mathematic education help google classroomon students mathematical reasoning abilities. The learning process uses an approach realistic mathematic education help google classroom can be used as an alternative learning to improve students mathematical reasoning abilities.